Roles, Responsibilities, and Functions of Village Health, Sanitation, and Nutrition Committees in India: A Qualitative Evidence Synthesis - Sathish Rajaa; Senthilkumar Ramalingam; Maulik Chokashi; Tushar Mokashi (Indian Journal of Public Health)
National Health Mission instituted the Village Health, Sanitation, and Nutrition Committees (VHSNCs) in 2005, with an aim of ensuring health and well-being for local communities in India. There is a lack of concrete evidence on the functioning of VHSNCs at a national level. Thus, this study was undertaken to outline the roles, responsibilities, and functions of VHSNCs in India. We conducted a comprehensive data search in Medline, Cochrane Library, ScienceDirect, EMBASE, and Google Scholar between 2005 and August 2021. All peer-reviewed qualitative studies that reported the roles, responsibilities, functions, and good practices of VHSNCs from India were included in our review. Critical Appraisal Skills Programme checklist was used to assess the quality of individual studies. In total, we included 15 studies (including 1100+ VHSNCs) from various states of India. Our review highlighted that the majority of the VHSNCs functioned without a clear-cut definition of roles and responsibilities had irregular meetings and workforce shortage. There was a lack of inclusivity, accountability, and delay in the processing of untied funds. The included studies have showed that VHSNCs were involved health promotional activities such as formulation and implementation of village health plans, delivery of services through public distribution systems, ensuring safe drinking water and sanitary supervision, and identification and referral of malnourished children. Our review highlights the crucial role that VHSNCs play in improving the health outcomes of rural populations and underscores the need for continued support and capacity-building efforts to ensure their effectiveness.